The academic librarians' empowerment and engagement as research partners: a qualitative study - Talatu Rabasa,; A. Abrizah, (Malaysian Journal of Library and Information Science, 2024)
Academic librarians are seen as information providers, even where their provision is beyond the simple rule of providing access to information. This perception had not changed in Nigeria, even when academic librarians were accorded academic status and adopted an embedded librarianship model, which allows them to collaborate with the faculty. The need arises for how optimal the academic librarians can partner with faculty members in research. As a result, this study explored the source of academic librarians' engagement with their work role and empowerment for effective participation and collaboration, and enhance performance. The study employed a qualitative approach and purposively sampled 21 academic librarians from a major university in Nigeria. Data were generated through focus group discussions and interviews. The findings were structured around six (6) sources of empowerment themes and four (4) sources of engagement themes. Since this is the first study in Nigeria that articulates a manifestation of academic librarians as research partners, it has provided academic librarians with the necessary authority to enhance their performance in a research partnership and has paved the way for further research.